Unusual form of cutaneous infiltration by cancer - Zucchi, A.; Aimi, F.; Cardis, et al., A. (Acta Biomedica Atenei Parmensis, 2012)
Breast cancer is the most common visceral neoplasm which metastatizes in skin. Skin infiltration by breast cancer may appear as various types of neoplastic/inflammatory lesions, including plaques, pigskinlike areas, scirrhous morphea-like lesions, nodules, zosteriform lesions, and papulovescicles. An unusual form of cutaneous infiltration involving a mammary region bearing a post-mastectomy surgical skin scar is herein described: interestingly, such a cutaneous cancer involvement could not be included in the above classification, because it merely consisted of red-purple areas dealing with small telangiectasias, without any sign of inflammation.